Genetic variation in endocannabinoid signaling is associated with differential network‐level functional connectivity in youth. Issue 3 (8th September 2021) - Sisk, Lucinda M.; Rapuano, Kristina M.; Conley, May I.; Greene, Abigail S.; Horien, Corey; Rosenberg, Monica D.; Scheinost, Dustin; Constable, R. Todd; Glatt, Charles E.; Casey, B. J.; Gee, Dylan G.
Abstract: The endocannabinoid system is an important regulator of emotional responses such as fear, and a number of studies have implicated endocannabinoid signaling in anxiety. The fatty acid amide hydrolase (FAAH) C385A polymorphism, which is associated with enhanced endocannabinoid signaling in the brain, has been identified across species as a potential protective factor from anxiety. In particular, adults with the variant FAAH 385A allele have greater fronto‐amygdala connectivity and lower anxiety symptoms. Whether broader network‐level differences in connectivity exist, and when during development this neural phenotype emerges, remains unknown and represents an important next step in understanding how the FAAH C385A polymorphism impacts neurodevelopment and risk for anxiety disorders. Here, we leveraged data from 3, 109 participants in the nationwide Adolescent Brain Cognitive Development Study℠ (10.04 ± 0.62 years old; 44.23% female, 55.77% male) and a cross‐validated, data‐driven approach to examine associations between genetic variation and large‐scale resting‐state brain networks. Our findings revealed a distributed brain network, comprising functional connections that were both significantly greater (95% CI for p values = [<0.001, <0.001]) and lesser (95% CI for p values = [0.006, <0.001]) in A‐allele carriers relative to non‐carriers. Furthermore, there was a significant interaction between genotype and the summarized connectivity of functional connections that were greater in A‐allele carriers, such that non‐carriers with connectivity more similar to A‐allele carriers (i.e., greater connectivity) had lower anxiety symptoms ( β = −0.041, p = 0.030). These findings provide novel evidence of network‐level changes in neural connectivity associated with genetic variation in endocannabinoid signaling and suggest that genotype‐associated neural differences may emerge at a younger age than genotype‐associated differences in anxiety. Abstract : This study leveraged data from 3, 109 youth to examine associations between genotype, functional connectivity, and anxiety. Results demonstrate evidence of network‐level changes in neural connectivity associated with genetic variation in endocannabinoid signaling and suggest that genotype‐associated neural differences may emerge at a younger age than genotype‐associated differences in anxiety.